Microarray analysis identifies defects in regenerative and immune response pathways in COPD airway basal cells. Issue 4 (7th December 2020) - Pineau, Fanny; Shumyatsky, Gabriella; Owuor, Nicole; Nalamala, Nisha; Kotnala, Sudhir; Bolla, Sudhir; Marchetti, Nathaniel; Kelsen, Steven; Criner, Gerard J.; Sajjan, Uma S.
Background: Airway basal cells are specialised stem cells and regenerate airway epithelium. Airway basal cells isolated from patients with COPD regenerate airway epithelium with an abnormal phenotype. We performed gene expression analysis to gain insights into the defective regenerative programme in COPD basal cells. Methods: We conducted microarray analysis and compared COPD versus normal basal cells to identify differentially regulated genes (DEGs) and the enriched biological pathways. We determined the correlation of DEGs with cell polarisation and markers of ciliated and goblet cells. HOXB2 was knocked down in 16HBE14o− cells and monitored for polarisation of cells. HOXB2 expression in the lung sections was determined by immunofluorescence. Results: Comparison of normal and COPD basal cell transcriptomic profiles highlighted downregulation of genes associated with tissue development, epithelial cell differentiation and antimicrobial humoral response. Expression of one of the tissue development genes, HOXB2 showed strong correlation with transepithelial resistance and this gene was downregulated in COPD basal cells. Knockdown of HOXB2, abrogated polarisation of epithelial cells in normal cells. Finally, HOXB2 expression was substantially reduced in the bronchial epithelium of COPD patients. Conclusions: Defect in gene signatures involved in tissue development and epithelial differentiation were implicated in COPD basal cells. One of the tissue developmental genes, HOXB2, is substantially reduced in bronchial epithelium of COPD patients. Since HOXB2 contributes to airway epithelial cell polarisation, we speculate that reduced expression of HOXB2 in COPD may contribute to abnormal airway epithelial regeneration in COPD. COPD airway basal cells show downregulation of gene sets that are involved in intercellular junctions, epithelial differentiation and immune responses, highlighting the possible mechanisms of defective airway epithelial repair in COPD https://bit.ly/3kneloj